Emotion Regulation, Cognitive Closure and Compliance of Spouses in Relationship Conflict - roth, roni laslo (Advances in Social Sciences Research Journal, 2017)
This study was aimed to examine the relationships between emotion regulation and compliance among spouses in conflict. Furthermore, because compliance in conflict situations has been associated with individual differences in cognitive closure and emotions, we examined how these factors modulate the effect of emotion regulation on compliance. To this end, 70 praticipates, randomly assigned to reappraisal and control groups, reported the influence tactics they would comply, their affective state and their cognitive closure level. Results indicated that as compared to control, reappraisal strengthened the tendency to comply during conflict and that this effect was stronger among participants with low cognitive closure. Moreover, the interaction between emotion regulation and cognitive closure on harsh influence tactics was mediated by inward-directed negative affect, suggesting that the reappraisal instruction promoted better resiliency to negative affect among high cognitive closure participants. We discuss the role of emotion regulation techniques in treatment and in interpersonal relationships.